A survey of theological seminary libraries belonging to Asia Graduate School of Theology (AGST) with implications for interlibrary loan policy - Capuno, Mary Ruth A. (2011)
The term interlibrary loan encompasses both borrowing and lending - the requesting of materials and the sending of materials, including provision of reproductions. This study is about the theological seminary libraries belonging to Asia Graduate School of Theology (AGST) Consortium. A survey questionnaire was used to obtain data about the collection of the library as well as the services they give to their patrons. The data collected from the questionnaire was compiled, tabulated and analyzed.